(untitled) (Fiep Bulletin - online, 2012)
Introduction: Obesity is a public health problem that involves a large number of Brazilians of all ages. It is the most important nutritional disorder in the developed world, with approximately 10% of its population are considered obese. In the individual with morbid obesity, excess stored fat in the abdominal cavity exerts direct mechanical effect on the rib cage and diaphragm, restricting chest expansion, with consequent reduction in lung volumes, even in the face of the respiratory system without pathological changes. Objective: To measure lung function by spirometry checking the contents of FVC, FEV1, FEV1/FVC, FEF 25-75 in patients pre-operative bariatric surgery. Methodology: The treatment was performed at the Rehabilitation Center of Assisi School Gurgacz - FAG sector in CardiopulmonaryPhysical Therapy. The sample consisted of nine women and three men 18 to 50 years, previously evaluated by the gastroenterologist, duly forwarded to FAG for physical therapy and released for physical activity in soil and pulmonary rehabilitation. All are in line to perform bariatric surgery. Results: Responses were analyzed and found himself Average FEV1 of ± 2.77, ± 3.01 for FVC, FEV1/FVC and FEF25 of ± 94.5% - 75% ± 2.28. Conclusion: This study answered the research objectives and proved to be beneficial when used as a means of preparation for the pre-operative bariatric surgery, with an increase lung capacity and volume of patients ventilated. It is suggested to repeat the study with a larger sample of individuals.